Effect of problem-based learning model on critical thinking and Math learning motivation - Muhammad Sabiq; Edy Surya; E. Elvis Napitupulu (Himpunan Pengembang Kurikulum Indonesia, 2025)
Critical thinking ability and learning motivation are two essential aspects of mathematics learning that are closely interrelated. Low cognitive and affective engagement among students is often caused by instructional approaches that fail to support higher-order thinking activities. This study aims to analyze the influence of the Problem-Based Learning model on students' critical thinking ability and mathematics learning motivation. The research employed a quantitative approach using a quasi-experimental design involving two classes of seventh-grade students at MTs Jam’iyah Mahmudiyah Tanjung Pura. The instruments included essay tests to assess critical thinking skills and Likert-scale questionnaires to measure students' motivation. The results of the normality and homogeneity tests confirmed that the data were normally distributed and had homogeneous variance, allowing the use of Two-Way ANOVA and the Mann-Whitney test for further analysis. The findings indicated that Problem-Based Learning was significantly more effective than direct instruction in enhancing both critical thinking and motivation. Moreover, an interaction effect between students’ prior mathematical ability and the learning model was observed. This research highlights the importance of implementing problem-based learning strategies that respond to individual differences in students’ needs and abilities. Abstrak Kemampuan berpikir kritis dan motivasi belajar merupakan dua aspek penting dalam pembelajaran matematika yang saling berhubungan. Rendahnya keterlibatan kognitif dan afektif siswa dalam proses belajar sering kali disebabkan oleh pendekatan pembelajaran yang tidak memfasilitasi aktivitas berpikir tingkat tinggi. Penelitian ini bertujuan untuk menganalisis pengaruh model Problem-Based Learning terhadap kemampuan berpikir kritis dan motivasi belajar matematika siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan desain eksperimen semu dan melibatkan dua kelas siswa tingkat VII di MTs Jam’iyah Mahmudiyah Tanjung Pura. Instrumen yang digunakan mencakup tes uraian untuk mengukur kemampuan berpikir kritis serta angket skala Likert untuk menilai motivasi belajar matematika siswa. Hasil analisis menunjukkan bahwa data berdistribusi normal dan memiliki varians yang homogen, sehingga pengujian menggunakan ANOVA dua jalur dan uji Mann-Whitney dapat dilaksanakan. Temuan menunjukkan bahwa pembelajaran menggunakan model Problem-Based Learning secara signifikan lebih efektif dibandingkan pembelajaran langsung dalam meningkatkan kedua variabel tersebut. Interaksi antara kemampuan awal matematika dan model pembelajaran juga berpengaruh terhadap hasil belajar. Penelitian ini memperkuat urgensi penerapan pendekatan pembelajaran berbasis masalah yang adaptif terhadap kebutuhan dan kemampuan siswa. Kata Kunci: berpikir kritis; Matematika; motivasi belajar; problem-based learning